Studi Komparatif Keuangan Bank Syariah Mandiri Periode 2013-2018 dengan Metode Common Size - Wahyuni, Eka Sri; Ermayni, Mita (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
This study aims to determine the comparison of the financial performance of Bank  Syariah Mandiri before (2013-2015) and after (2016-2018) the implementation of hedging using the common size method. This type of research is a quantitative study using a comparative approach method based on secondary data in the form of financial reports on Bank Syariah Mandiri for the period 2013-2018 obtained from the official website of Bank Syariah Mandiri. Hypothesis testing is the paired sample t-test. The results of this study indicate that there are differences in bank financial performance before and after the application of hedging in terms of assets, there is no difference in bank financial performance before and after the application of hedging in terms of liabilities and there are differences in financial performance. banks before and after the implementation of hedging in terms of profit and loss